Proposal of 0.5 mg of protein/100 g of processed food as threshold for voluntary declaration of food allergen traces in processed food-A first step in an initiative to better inform patients and avoid fatal allergic reactions: A GA(2)LEN position paper - Zuberbier Torsten; Dörr Tamara; Aberer Werner; Alvaro Montserrat; Angier Elizabeth; Arasi Stefania; Arshad Hasan; Ballmer-Weber Barbara; Bartra Joan; Beck Lisa; Bégin Philippe; Bindslev-Jensen Carsten; et al. (Wiley, 2022)
Background
Food anaphylaxis is commonly elicited by unintentional ingestion of foods containing the allergen above the tolerance threshold level of the individual. While labeling the 14 main allergens used as ingredients in food products is mandatory in the EU, there is no legal definition of declaring potential contaminants. Precautionary allergen labeling such as “may contain traces of” is often used. However, this is unsatisfactory for consumers as they get no information if the contamination is below their personal threshold. In discussions with the food industry and technologists, it was suggested to use a voluntary declaration indicating that all declared contaminants are below a threshold of 0.5 mg protein per 100 g of food. This concentration is known to be below the threshold of most patients, and it can be technically guaranteed in most food production. However, it was also important to assess that in case of accidental ingestion of contaminants below this threshold by highly allergic patients, no fatal anaphylactic reaction could occur. Therefore, we performed a systematic review to assess whether a fatal reaction to 5mg of protein or less has been reported, assuming that a maximum portion size of 1kg of a processed food exceeds any meal and thus gives a sufficient safety margin.
Methods
MEDLINE and EMBASE were searched until 24 January 2021 for provocation studies and case reports in which one of the 14 major food allergens was reported to elicit fatal or life-threatening anaphylactic reactions and assessed if these occurred below the ingestion of 5mg of protein. A Delphi process was performed to obtain an expert consensus on the results.
Results
In the 210 studies included, in our search, no reports of fatal anaphylactic reactions reported below 5 mg protein ingested were identified. However, in provocation studies and case reports, severe reactions below 5 mg were reported for the following allergens: eggs, fish, lupin, milk, nuts, peanuts, soy, and sesame seeds.
Conclusion
Based on the literature studied for this review, it can be stated that cross-contamination of the 14 major food allergens below 0.5 mg/100 g is likely not to endanger most food allergic patients when a standard portion of food is consumed. We propose to use the statement “this product contains the named allergens in the list of ingredients, it may contain traces of other contaminations (to be named, e.g. nut) at concentrations less than 0.5 mg per 100 g of this product” for a voluntary declaration on processed food packages. This level of avoidance of cross-contaminations can be achieved technically for most processed foods, and the statement would be a clear and helpful message to the consumers. However, it is clearly acknowledged that a voluntary declaration is only a first step to a legally binding solution. For this, further research on threshold levels is encouraged.